1994
DOI: 10.1063/1.112092
|View full text |Cite
|
Sign up to set email alerts
|

Efficient blue electroluminescence from a fluorinated polyquinoline

Abstract: High efficiency blue electroluminescence is demonstrated from a polyquinoline ether, a new class of soluble, electroluminescent, polyaromatic polymer. Multilayer devices (consisting of hole and electron transport layers in addition to the emissive polyquinoline layer) show an internal quantum efficiency in excess of 4% at 450 nm. Light emitted from these devices is easily visible in room light with luminence levels of 30 cd/m2 at 55 V with a current density of 9 mA/cm2. The transport layers are shown to serve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
107
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(109 citation statements)
references
References 19 publications
2
107
0
Order By: Relevance
“…6(a) and (b), respectively. The electrical and optical characteristics of these LEDs have been previously described [23].…”
Section: Multilayer Organic Ledmentioning
confidence: 99%
“…6(a) and (b), respectively. The electrical and optical characteristics of these LEDs have been previously described [23].…”
Section: Multilayer Organic Ledmentioning
confidence: 99%
“…Therefore, balanced charge injections from both electrodes are important for high device efficiencies [13,14]. It was reported that the HOMO-LUMO energy levels could be lowered for balanced charge injections by the introduction of electron-withdrawing substituents onto the conjugated main chain of the polymer.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, conjugated polymers have attracted great interest due to most of the polymers can be processed from solution at room temperature and their potential application in developing large scopes, flexible, lightweight and low cost organic light emitting diodes (OLEDs) and organic solar cells (OSCs) [1,2]. Unfortunately, the electrical and optical properties of these polymers do not compare to those of inorganic semiconductor materials, thus, polymer-based devices have performed poorly in common.…”
Section: Introductionmentioning
confidence: 99%